Cyber Notary: Adaptation to Changes in Notary Practices in Indonesia - Abdillah, Satrio; Ghapa, Norhasliza; Makhtar, Maheran (Universitas Negeri Gorontalo, 2026)
This study investigates the adaptation of notary practices in Indonesia in response to digital transformation, focusing on implementing cyber notary systems. This research focuses on analyzing the opportunities, challenges, and integration of traditional legal principles in the implementation of cyber notaries in Indonesia. Furthermore, this study aims to formulate a framework that supports the effective, safe, and sustainable implementation of cyber notaries in accordance with applicable legal provisions. This research uses normative legal methods with a conceptual and legislative approach to analyze the suitability of existing regulations for the implementation of cyber notaries in Indonesia. Thematic analysis using NVivo 12 Plus was used to identify patterns and relationships between themes from secondary legal sources, which were then validated normatively. The findings reveal that while cyber notary adoption can enhance notarial service delivery, significant obstacles remain, including limited digital literacy, inadequate technological infrastructure, and insufficient legal frameworks. The research highlights the necessity of comprehensive legal reform and increased public awareness to ensure the legality, fairness, and transparency of electronic document management. By proposing a legal framework tailored to Indonesia’s civil law context, this study contributes to the discourse on legal modernization and offers policy recommendations to strengthen public trust in digital legal services. This research normatively contributes to formulating a clear, legitimate, and transparent legal framework for cyber notaries in Indonesia.